Using A Tiered Approach for Implementing Networked Learning Communities: A Case Study on Developing the Capacity of Leaders to Implement Systemwide Innovations within International Training and Development Programs - James C. Anderson II; Eric Kaufman; Jama Coartney; Shreya Mitra; Carol Cash (Journal of International Agricultural and Extension Education, 2020)
This case study demonstrates how change agents can utilize networked learning communities (NLCs) with shared leadership to provide the structural supports for learning and influence the implementation of innovations within a social system. Our focus is the Department of Defense Education Activity (DoDEA), a large school system operating 164 accredited schools domestically and internationally. As part of their systemic priority of implementing innovations for educational improvement, DoDEA worked with extension specialists to create NLCs for instructional leaders using the Engelbart’s Organizational Learning and Improvement Schema. The schema is a three-tiered approach to non-formal learning that facilitates leader capacity building at the individual, team, and systemwide levels. To support these learning communities, DoDEA also created regional support teams or opinion leaders to assist with the implementation of systemwide educational technologies through non-formal professional learning. Focus group discussions provided insights on the impact of this model as a mechanism for diffusing educational innovations throughout the system. Findings suggest that implementation of this approach in other international training and development settings can yield positive impacts on the innovation-decision process.
Keywords: Shared leadership; international training & development; social learning; systemicchange; Diffusion of Innovation